3 ( 9 + 3 ∣ x ∣ + ∣ x + 4 ∣ ) = 3 ∣ x + 4 ∣ + 3 ∣ x ∣ + 4
Find the sum of all values of x satisfying the above equation
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
3 ( 9 + 3 I x I + I x + 4 I ) = 3 I x + 4 I + 3 I x I + 4 ⟹ 2 7 + 3 I x I + I x + 4 I + 1 = 3 I x + 4 I + 3 I x I + 1 . 2 7 ⟹ 3 I x I + 1 ( 3 I x + 4 I − 2 7 ) = 3 I x + 4 I − 2 7 n o w t h e r e a r e t w o w a y s i n w h i c h t h i s e q u a t i o n w o u l d s a t i s f y c a s e 1 − 3 I x I + 1 = 1 ⟹ I x I + 1 = 0 ⟹ I x I = − 1 w h i c h i s n o t p o s s i b l e s i n c e a b s o l u t e v a l u e o f a n y n u m b e r i s a l w a y s p o s i t i v e . s o t h i s c a s e i s n o t p o s s i b l e . c a s e 2 − 3 I x + 4 I − 2 7 = 0 ⟹ 3 I x + 4 I = 3 3 ⟹ I x + 4 I = 3 w h i c h y e i l d s t w o s o l u t i o n s x = − 1 , − 7 s i n c e n o o t h e r c a s e i s p o s s i b l e . t h e s e w i l l b e t h e o n l y t w o s o l u t i o n s . s o t h e f i n a l a n s w e r , i . e t h e i r s u m w o u l d b e − 1 + − 7 = − 8
L e t a = 3 ∣ x ∣ a n d b = 3 ∣ x + 4 ∣ ⇒ 3 ( 9 + a b ) = b + 8 1 a ⇒ 2 7 − b = 3 a ( 2 7 − b ) ∴ a = 3 1 o r b = 2 7 N o w a = 3 1 ⇒ 3 ∣ x ∣ = 3 − 1 ⇒ ∣ x ∣ = − 1 w h i c h i s i m p o s s i b l e a s ∣ x ∣ ≥ 0 ∀ x T h u s b = 2 7 ⇒ 3 ∣ x + 4 ∣ = 3 3 ⇒ ∣ x + 4 ∣ = 3 , ∴ x + 4 = ± 3 ⇒ x = − 7 o r − 1 T h u s t h e s u m o f a l l r e a l s o l u t i o n s = − 1 + − 7 = − 8
@Aditya Dhawan I've converted your comment into a solution.
That was awesomely simple
Problem Loading...
Note Loading...
Set Loading...
Let f ( x ) = 3 ( 9 + 3 ∣ x ∣ + ∣ x + 4 ∣ ) − 3 ∣ x + 4 ∣ − 3 ∣ x ∣ + 4 = 0 , We have to consider 3 cases when f ( x ) changes form.
Case 1: x > 0
3 ( 9 + 3 x + x + 4 ) − 3 x + 4 − 3 x + 4 3 3 + 3 5 ( 3 x ) 2 − 2 ˙ 3 4 ( 3 x ) 9 ( 3 x ) 2 − 6 ( 3 x ) + 1 ( 3 ( 3 x ) − 1 ) 2 3 x ⇒ x = 0 = 0 = 0 = 0 = 3 1 = − 1 < 0 rejected
Case 2: − 4 < x ≤ 0
3 ( 9 + 3 − x + x + 4 ) − 3 x + 4 − 3 − x + 4 3 3 + 3 5 − 3 4 ( 3 x ) − 3 4 ( 3 − x ) 3 ( 3 x ) 2 − 1 0 ( 3 x ) + 3 ( 3 ( 3 x ) − 1 ) ( ( 3 x ) − 3 ) 3 x = 0 = 0 = 0 = 0 = { 3 1 3 ⇒ x = − 1 ∈ ( − 4 , 0 ] ⇒ x = 1 > 0 accepted rejected
Case 2: x ≤ − 4
3 ( 9 + 3 − x − x − 4 ) − 3 − x − 4 − 3 − x + 4 3 3 + 3 − 3 ( 3 − x ) 2 − 3 − 4 ( 3 − x ) − 3 4 ( 3 − x ) 3 ( 3 − x ) 2 − 6 5 6 2 ( 3 − x ) + 2 1 8 7 ( 3 ( 3 − x ) − 1 ) ( ( 3 − x ) − 2 1 8 7 ) 3 − x = 0 = 0 = 0 = 0 = { 3 1 3 7 ⇒ x = 1 > − 4 ⇒ x = − 7 < − 4 rejected accepted
Therefore the sum of solutions is − 1 − 7 = − 8